Problems of in vitro Antibiotic Susceptibility Compliance with Efficacy of Chemotherapy in Infections Due to Pathogenic Burkholderias - V. I. Ilyukhin; T. V. Senina; M. N. Trushkina; E. V. Shubnikova; YU. V. Antonov; N. V. Andropova (Антибиотики и Химиотерапия)
Among the known species of Burkholderia only two are obligate pathogens, i. e. B.mallei and B.pseudomallei, causative agents of glanders and melioidosis respectively. The other species are saprophytes as natural inhabitants of water reservoirs and soil, still capable of causing opportunistic infections in humans and animals under definite conditions. All the species of Burkholderia are characterized by high resistance to antibacterials, including antibiotics. By the MICs, the most efficient chemotherapeutics against pathogenic burkholderias are tetracyclines, fluoroquinolones, penems and combined sulfanilamides. In the treatment of experimental glanders and melioidosis the set of the effective drugs had the inverse variation dependence on the infection severity and the desease process rate. Co-trimoxasole showed the best results, then followed doxicycline, ciprofloxacin and ceftazidime in the diminishing succession. The modification of the method for determination of antibiotic susceptibility with addition of native blood to the medium and the subculture under the atmosphere of 5% CO2 was shown useful in estimation of the prospects of the use of chemotherapeutics for the treatment of Burkholderia infections.